ISOLATION AND CHARACTERIZATION OF LEAF EXTRACT OF DERRIS TRIFOLIATA - R.SUGANYA; Dr. SHALEESHA A. STANLEY (International Journal of Pharma and Bio Sciences, 2015)
Derris trifoliata belongs to the family Fabaceae of the order Papilionoideae. D. trifoliata is used in local medicine in India as a stimulant, antispasmodic and counter-irritant, and against rheumatism, chronic paralysis and dysmenorrhoea. The bioactive principle present in the leaves of Derris trifoliata was isolated and characterized in the present study. The powdered leaves were repeatedly extracted in methanol. The crude methanolic extract upon separation through silica gel column chromatography yielded 70 fractions which were then separated further by thin layer chromatography and isolated three different compounds. These fractions were further characterized by high performance thin layer chromatography and the Rf values are identified accurately for individual peaks. This yields the complete phytochemical characterization of the methanol extracts of Derris trifoliata.The study attempts to identify the new compounds in this plant that revealed three compounds. The purity of the compounds was determined for the effective utilization of the compounds in the production of novel pharmaceutical preparations.